Faktor Keberhasilan Usaha UMKM Jajanan Asing Kaki Lima di Kota Serang - Prasatya, Fauzan Anggi; Muhandri, Tjahja; Cahyadi, Eko Ruddy (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
The competition of food business is currently very strict and diverse product innovations. To achieve the market share and win the business competition needs to know the affecting success factors. This study has two main objectives that include the following to: (1) mapping the characteristics of non traditional street food entrepreneur in Serang City, (2) identify the most affected success factor of non traditional street food business. Sampling method was used by purposive sampling 100 respondents. The analytical method used descriptive analysis and binary logistic regression. This research showed most of successful vendor are woman, because they are very conscientious than mens and tend to avoid risk. Affecting success factors on non traditional street food business were price of the product, business name and start up capital.